Information and methodological provision of statistical analysis of the intensity of subsoil use in Ukraine in accordance with the goals of sustainable development in the pre-war and war period - I.R.; Yu.S.; R.M. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
It has been established that the information base for the statistical analysis of the intensity of subsoil use is aggregated statistical information based on individual statistical data contained in the Tax Declaration on rent payments with its annexes. An analysis of the structure of tax revenues of rent payments to local budgets by region of Ukraine for 2021 was carried out. It was found that Dnipropetrovsk region has the largest share of rent payments as tax revenue of local budgets, and Odesa region has the lowest. Regions were grouped according to the components of the rent in terms of natural resources. Zhytomyr region is the leader in terms of tax revenue from rent for the use of forest resources, Zaporizhia region for water resources, Poltava region for national importance, and Kyiv region for subsoil of local importance. The distribution of regions according to the amount of rent for the use of subsoil of national and local importance is given. It was found that the vast majority of local budgets have a predominance of the amount of rent received for the use of subsoil of national importance over local ones, except for Kyiv, Ternopil and Chernivtsi regions. The regions of Ukraine were grouped by specialization in subsoil use based on the local budgets of each region for 2021. Ten regions specialize in the use of subsoil of national significance. Nine regions have the highest share of tax revenues from rent for the use of forest resources. Four regions have specialization in the use of water resources. Subsoil of local importance is a priority natural resource for the Ternopil region. An assessment of the profitability of mining enterprises among all enterprises of the extractive industry and the development of quarries by region during the period of martial law was carried out. It was found that in most regions of Ukraine in 2022, more than half of the mining enterprises were unprofitable.